The cost of a taxi ride can be calculated using the equation c = 1.75 + (m - 1/8) * 8 * 0.30, where c represents the total cost and m represents the total miles driven. Solving this equation for m when the total cost is $7.75 would yield the number of miles driven.
Explanation:The subject of this question is the creation of an equation to calculate the cost of a taxi ride. According to the question, a taxi charges $1.75 for the first 1/8 mile and $0.30 for each additional 1/8 mile. First, we need to convert miles to 1/8 miles, since the pricing is based on this fraction. We know that each full mile is equal to 8 fractions of 1/8 mile. Therefore, to convert miles to 1/8 miles, we multiply the number of miles by 8.
Given this pricing structure, the costs associated with additional miles driven beyond the first 1/8 mile (which are already accounted for by the initial $1.75), can be represented by (m-1/8)*8*0.30. Here, (m-1/8) represents the additional miles traveled beyond the first 1/8 mile, and multiplying this by 8 converts these miles into 1/8 miles.
The total cost, c, can thus be represented by the equation c = 1.75 + (m - 1/8) * 8 * 0.30. If a ride cost $7.75, we can substitute this cost into the equation and solve for m to find the number of miles driven. This would give us the equation: 7.75 = 1.75 + (m - 1/8) * 8 * 0.30.
Learn more about Algebra here:https://brainly.com/question/32436021
#SPJ2
write an equation for the line parallel to y= -2x+1 that contains (-2,5)
Answer:
y = - 2x + 1
Step-by-step explanation:
Parallels line have the same slope, when an equation is in the form y= mx + b, m is the slope. In this problem slope = - 2
Now with the slope what is missing is the y-intercept, the problem says that the line contains the point (-2, 5), replacing that point in the equation you can solve it to find the y-intercept
y = mx + b
5 = (-2)(-2) + b
5 = 4 + b
1 + b
y = - 2x +1
Two parallel lines are intersected by a third line so that angles 1 and 5 are congruent. 2 parallel horizontal lines are intersected by a third line. On the first horizontal line where the third line intersects, 4 angles are created. Labeled clockwise, from uppercase left, the angles are 1, 2, 4, 3. On the second horizontal line, where the third line intersects, 4 angles are created. Labeled clockwise, from uppercase left, the angles are 5, 6, blank, blank. Which statement is true about angles 3 and 5? They are acute. They are congruent. They are complementary. They are supplementary.
Answer:
"They are supplementary" ⇒ last answer
Step-by-step explanation:
* Look to the attached figure
- Two parallel horizontal lines are intersected by a third line
- The angles formed form intersection are labeled on the figure
- From the two parallel lines and
∠5 ≅ ∠1 ⇒ corresponding angles
m∠5 = m∠1
- A linear pair is two angles that are adjacent and form a line and
they are supplementary
∠1 and ∠3 form a line
∠1 and ∠3 are linear pair
* lets prove that ∠3 and ∠5 are supplementary
∵ m∠1 = m∠5 ⇒ corresponding angles
∵ ∠1 and ∠3 form a linear pair
∵ Linear pair are supplementary
∴ m∠1 + m∠3 = 180°
- By substitute ∠1 by ∠5
∴ m∠5 + m∠3 = 180
∴ ∠5 and ∠3 are supplementary
* The true statement is "They are supplementary"
Angles 3 and 5 are congruent because they are alternate interior angles formed by a transversal intersecting two parallel lines. This is supported by the Alternate Interior Angles Theorem.
To determine the relationship between angles 3 and 5 when two parallel lines are intersected by a transversal, we can use the properties of alternate interior angles.
Given that angles 1 and 5 are congruent, we identify that they are alternate interior angles formed by the transversal intersecting two parallel lines. By the Alternate Interior Angles Theorem, since the lines are parallel, angles 1 and 5 are congruent.Angles 3 and 5 in this setup are also alternate interior angles, and by the same theorem, they are congruent.
This leads us to the conclusion that:
Angles 3 and 5 are congruent.
Find x please!!!!!!!!!
The difference of a number and 12 is 30
Answer:
42
Step-by-step explanation:
Difference is substitution, so a number (x) minus 12 equals 30
x-12=30
Add 12 to both sides
x=42
The problem statement is a Mathematics subtraction problem. It can be solved by setting up a simple equation n - 12 = 30, where 'n' is the unknown number. By solving the equation, we find n = 42.
Explanation:The subject of the problem statement 'The difference of a number and 12 is 30' lies in the Mathematics field. When the problem says the 'difference of a number and 12 is 30', it means we are dealing with a subtraction expression. Here, we can write a simple equation to solve this. If we use 'n' to represent the unknown number, the equation will be: n - 12 = 30. To solve for n, we should add 12 to both sides of the equation to balance it. So, it will be n = 30 + 12, and hence n = 42. So, the number in the problem statement is 42.
Learn more about Subtraction here:https://brainly.com/question/20438352
#SPJ2
solve this problem y=(x-3)^2 when x=9
solve for x 2/x+1/2=3/4
which inequality symbols do i use for a-d if can help please comment picture of how number line will look
Answer:
a. <
b. >
c. >
d.<
Step-by-step explanation:
6 1/4 is less than 6 2/3
-3 is greater than -4
-5 is greater than -5.2
-5 is lesson that -4.8
Represent the geometric series using the explicit formula.
12, −36, 108, −324, …
f(n) = f(n − 1) ⋅ (−3)
f(n) = f(n − 1) ⋅ (3)
f(n) = 12 ⋅ (−3)(n−1)
f(n) = 12 ⋅ (3)(n−1)
The explicit formula for the geometric sequence 12, -36, 108, -324, ... is f(n) = 12 * (-3)^(n-1), where 'n' is the term number.
Explanation:The series provided is a geometric series. In a geometric series, each term after the first is found by multiplying the previous term by a fixed, non-zero number called the common ratio, denoted by 'r'. In our given series 12, -36, 108, -324, ..., you can determine that the common ratio (r) is -3. Now, using the formula for a geometric sequence given by f(n) = a * r^(n-1), where 'a' is the first term (12 in this case) and 'n' is the term number, we can write the explicit formula as
f(n) = 12 * (-3)^(n-1).
Learn more about Geometric Series here:https://brainly.com/question/30264021
#SPJ12
The geometric series is represented by the explicit formula f(n) = 12 * (-3)^(n-1)
Explanation:The given sequence is an example of a geometric progression where each term is found by multiplying the previous term by a constant ratio. In this case, the common ratio is -3.
The explicit formula for a geometric series is given by f(n) = a * r^(n-1), where 'a' is the first term and 'r' is the common ratio. In this sequence, the first term (a) is 12 and the common ratio (r) is -3.
Plugging in the values into the formula, we can write the explicit formula for this geometric series as f(n) = 12 * (-3)^(n-1).
Learn more about geometric series here:https://brainly.com/question/30264021
#SPJ12
What’s 1:6 equal too in two ways
Hey!
------------------------------------------------
Solution:
We can get two different ways of 1:6 by add +1:+6.
1 + 1 = 6 + 6
2:12
2 + 1 = 12 + 6
3:18
------------------------------------------------
Answer:
2:12 and 3:18
------------------------------------------------
Hope This Helped! Good Luck!
Draw a quick picture of 3 hundreds, 5 tens and 7 ones. What number does your quick picture show? Write in the three different ways
Answer:
The table represents the start of the division of
Step-by-step explanation: instgram mack.thrasher
In the figure attached, the quick picture can be seen. See the second picture for clarification.
Another way to represent that number is in a table format, as:
Hundreds tens ones
3 5 7
Finally, 3 hundreds 5 tens and 7 ones are equal to 300 + 50 + 7 = 357
How do I get from this guy 3/2/(15/4) to 2/5?
[tex]\bf \cfrac{~~\frac{3}{2}~~}{\frac{15}{4}}\implies \cfrac{~~\begin{matrix} 3 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}{~~\begin{matrix}2 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}\cdot \cfrac{\stackrel{2}{~~\begin{matrix} 4 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}}{\underset{5}{~~\begin{matrix} 15 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}}\implies \cfrac{2}{5}[/tex]
To simplify the expression 3/2/(15/4), first convert the division of fractions to multiplication by the reciprocal, giving (3/2) * (4/15). Multiply the numerators and denominators and then reduce the fraction by dividing both by their greatest common divisor. The simplified result is 2/5.
To simplify the expression 3/2/(15/4), you would follow these steps:
Understand that dividing by a fraction is the same as multiplying by its reciprocal. In this case, 15/4 is the divisor, so we take its reciprocal which is 4/15.Multiply the original fraction 3/2 by the reciprocal of 15/4 which is 4/15.Perform the multiplication: (3/2) * (4/15).First, simplify by multiplying the numerators together and the denominators together: 3 * 4 = 12 and 2 * 15 = 30.So, you have 12/30, which can be reduced. Divide both the numerator and denominator by their greatest common divisor (GCD), which is 6.12 / 6 = 2 and 30 / 6 = 5, therefore the fraction simplifies to 2/5.Following these steps results in the original expression 3/2/(15/4) simplifying to 2/5.
Simplify: 7 exponent9 7 exponent3
Answer:
7^9= 40,353,607
7*7*7*7*7*7*7*7*7=40,353,607
7^3 =343
7*7*7=343
Triangle J K L is shown. Angle J K L is a right angle. An altitude is drawn from point K to point M on side L J to form a right angle. The length of K M is 6 and the length of M J is 3. What is the length of line segment LJ? 9 units 12 units 15 units 18 units
Answer:
[tex]LJ=15\ units[/tex]
Step-by-step explanation:
see the attached figure to better understand the problem
step 1
Find the length side KJ
In the right triangle JKM
Applying the Pythagoras Theorem
[tex]KJ^{2}=JM^{2}+KM^{2}[/tex]
we have
[tex]JM=3\ units[/tex]
[tex]KM=6\ units[/tex]
substitute
[tex]KJ^{2}=3^{2}+6^{2}[/tex]
[tex]KJ^{2}=45}[/tex]
[tex]KJ=\sqrt{45}\ units[/tex]
simplify
[tex]KJ=3\sqrt{5}\ units[/tex]
step 2
Find the value of cosine of angle MJK in the right triangle JKM
[tex]cos(JKM)=JM/KJ[/tex]
substitute the values
[tex]cos(JKM)=\frac{3}{3\sqrt{5}}[/tex]
simplify
[tex]cos(JKM)=\frac{\sqrt{5}}{5}[/tex] -----> equation A
step 3
Find the value of cosine of angle MJK in the right triangle JKL
[tex]cos(JKM)=KJ/LJ[/tex]
we have
[tex]KJ=3\sqrt{5}\ units[/tex]
[tex]cos(JKM)=\frac{\sqrt{5}}{5}[/tex] ----> remember equation A
substitute the values
[tex]\frac{\sqrt{5}}{5}=\frac{3\sqrt{5}}{LJ}[/tex]
Simplify
[tex]LJ=5(3)=15\ units[/tex]
Answer:
The answer would be option C. 15 units :)
Step-by-step explanation:
Did it on edge :D
Hope this helps!
Evaluate this exponential expression.
4. (2 + 5)2 - 52 =
A. 46
B. 144
c. 8
D. 171
Answer:
B
Step-by-step explanation:
Given
4(2 + 5)² - 52
Evaluate the parenthesis
4 × 7² - 52 ← evaluate the exponent
4 × 49 - 52 ← evaluate the multiplication
= 196 - 52 ← evaluate the subtraction
= 144 → B
Answer: D 171
Step-by-step explanation:
Identify the rule for the following pattern:
99, 90, 81...
What is the slope of the line passing through the points
(-1,7) and (4,-1)
Answer:
(5 , -18)
Hope this helps.
From your vro Que
Answer: [tex]\dfrac{-8}{5}[/tex]
Step-by-step explanation:
The slope of a line passing through points (a,b) and (m,n) is given by :-
[tex]\text{Slope}=\dfrac{n-b}{m-a}[/tex]
Given points : (-1,7) and (4,-1)
Then, the slope of the line passing through the points (-1,7) and (4,-1) will be :-
[tex]\text{Slope}=\dfrac{-1-7}{4-(-1)}\\\\=\dfrac{-8}{4+1}\\\\=\dfrac{-8}{5}[/tex]
Hence, the required slope = [tex]\dfrac{-8}{5}[/tex]
What is the solution to the equation 3/7(x+3)+5=3x+2?
Answer:
5/3
Step-by-step explanation:
i added a picture that will help you solve it.
The solution to the equation[tex]\dfrac{3}{7}(x+3)+5=3x+2[/tex] when "x" is an unknown variable is [tex]\dfrac{5}{3} .[/tex]
Two algebraic expressions separated by an equal symbol between them and with the same value are called equations.
Example = 2x +4 = 12
here, 4 and 12 are constants and x is variable.
To solve the equation[tex]\dfrac{3}{7}(x+3)+5=3x+2[/tex] we can follow these steps:
Multiply \dfrac{3}{7} into the brackets or inside the parentheses
[tex][\dfrac{3}{7}x + \dfrac{3}{7}\times3] + 5 = 3x + 2[/tex]
[tex]\dfrac{3}{7}x +\dfrac {9}{7} + 5 = 3x + 2[/tex]
On solving we get,
[tex]\dfrac{3x+9}{7} = 3x +2-5[/tex]
[tex]\dfrac{3x+9}{7} = 3x -3[/tex]
On cross multiplication we get,
[tex]{3x+9} = 7(3x -3)[/tex]
Opening the parenthesis we get
[tex]{3x+9} = (21x -21)[/tex]
Taking the variables to one side and constants on the right side we get,
[tex]{9+21} = (21x -3x)[/tex]
On further solving we get,
30 = 18 x
Simplify and solve for x:
Divide both sides by 18, and we get
[tex]\dfrac{30}{18} = x[/tex]
Now, in standard form
[tex]\dfrac{5}{3} = x[/tex]
In decimals, we get 1.66666.
Therefore, the solution to the equation [tex]\dfrac{3}{7}(x+3)+5=3x+2[/tex] is [tex]\dfrac{5}{3}[/tex].
Learn more about equations here :
https://brainly.com/question/14686792
#SPJ2
The cost to rent a car for a day is an initial cost of $35 and $0.25 per mile driven write an equation that represents to the cost of the car rental what is the total cost if you drove 250 miles
Answer:
$35 + $0.25m is the equation
If you drove 250 miles, it would cost $97.50
Step-by-step explanation:
250 * 0.25 = 62.5
62.5 + 35 = 97.5
Sketch a cube with 3 cm
Answer:
Step-by-step explanation: is This what you want?
4. Thirty divided by seven times a number
A. 30 + 7n
B. in
30
30(7n)
None of the above
30:7.
Answer:
30/7n
Step-by-step explanation:
let n be the no.
seven times a no. is 7n
so ans is 30/7n
ix is at least four more than a number. Which inequality represents this sentence? Question 20 options: a) 4 ≤ n + 6 b) 6 ≤ n + 4 c) 4 ≥ n + 6 d) 6 ≥ n + 4
Answer:
d) 6 ≥ n + 4
Step-by-step explanation:
Let n be the unknown number,
4 more than n = 4 + n
In inequality we use '≥' to represent greater than equal to or at least,
Thus,
Six is at least four more than a number.
⇒ 6 ≥ 4 more than n
⇒ 6 ≥ 4 + n
Which is the required inequality that represents the given statement,
OPTION d) is correct.
Answer:
b) 6 ≥ n + 4
Step-by-step explanation:
Determine the slope and the y intercept. Y= -2. Then use the slope and the y- intercept to graph the equation
Answer:
y-intercept: [0, -2]; 0 = m
Step-by-step explanation:
Anything set to equal y is what is known as a zero rate of change [slope] because it is a horizontal line.
I am joyous to assist you anytime.
which is greater 8.2 or 8.23
8.23 because of you add 0 after the 8.2 that will make it 8.20.
Hope it makes sense :)
Find x- and y-intercepts. Write ordered pairs representing the points where the line crosses the axes. x+y=6
Answer:
x-intercept = 6 → (6, 0)y-intercept = 6 → (0, 6)Step-by-step explanation:
x + y = 6
x-intercept is for y = 0. Substitute:
x + 0 = 6
x = 6
y-intercept is for x = 0. Substitute:
0 + y = 6
y = 6
1.) Michelle works at Bloomingdale's and earns a 20% commission for her daily sales. Yesterday, Michelle
sold $2,235 worth of merchandise. What was her commission?
Answer:
$447
Step-by-step explanation:
2,235 multiplied by .20
write a linear equation in slope -intercept form that passes through the points (-8,4) (1,-5)
[tex]\bf (\stackrel{x_1}{-8}~,~\stackrel{y_1}{4})\qquad (\stackrel{x_2}{1}~,~\stackrel{y_2}{-5}) \\\\\\ \stackrel{slope}{m}\implies \cfrac{\stackrel{rise} {\stackrel{y_2}{-5}-\stackrel{y1}{4}}}{\underset{run} {\underset{x_2}{1}-\underset{x_1}{(-8)}}}\implies \cfrac{-9}{1+8}\implies \cfrac{-9}{9}\implies -1[/tex]
[tex]\bf \begin{array}{|c|ll} \cline{1-1} \textit{point-slope form}\\ \cline{1-1} \\ y-y_1=m(x-x_1) \\\\ \cline{1-1} \end{array}\implies y-\stackrel{y_1}{4}=\stackrel{m}{-1}[x-\stackrel{x_1}{(-8)}]\implies y-4=-(x+8) \\\\\\ y-4=-x-8\implies y=-x-4[/tex]
positive whole numbers less than 9
4 can be one too because its less than 9 and its a whole number
Hope it helps :)
Which of the following values is the solution to the equation -35x = -105 ? 3 -3
Answer:
3.
Step-by-step explanation:
-35x = -105
Divide both sides by -35:
x = -105/-35
= 3.
The solution to the equation is x = 3.
What is an equation?Two or more expressions with an equal sign are defined as an equation.
The given equation is -35x = -105.
Solve the equation as follows:
-35x = -105
35x = 105
x = 105/35
x = 3
Hence, the solution to the equation is x = 3.
Learn more about equations here:
https://brainly.com/question/10413253
#SPJ2
is √10 rational or irrational
√10 is irrational because a rational number is a number that is a/b where a and b are integers and b is a nonzero number.√10 does not follow this.
If you need a better explanation just as in the comments.
Happy to help! Please mark as BRAINLIEST! Thanks
Solve 6+2x^2-3x=8x^2
Answer: 6x^2+3x-6
Step-by-step explanation:
6+2x^2-3x=8x^2
-2x^2. -2x^2
6-3x=6x^2
= 6x^2+3x-6
Answer:
Step-by-step explanation: